2016
DOI: 10.1039/c6tb00783j
|View full text |Cite
|
Sign up to set email alerts
|

Approaches for building bioactive elements into synthetic scaffolds for bone tissue engineering

Abstract: Bone tissue engineering (BTE) is emerging as a possible solution for regeneration of bone in a number of applications. For effective utilization, BTE scaffolds often need modifications to impart biological cues that drive diverse cellular functions such as adhesion, migration, survival, proliferation, differentiation, and biomineralization. This review provides an outline of various approaches for building bioactive elements into synthetic scaffolds for BTE and classifies them broadly under two distinct scheme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 167 publications
(203 reference statements)
0
41
0
Order By: Relevance
“…3,4 The synthetic scaffolds have convenient sources, good safety and non-immunogenicity, therefore, various synthetic scaffolds such as inorganic ceramics, bone cements, and metal implants have been introduced as the substrates for bone defects. 5,6 These synthetic scaffolds provide physical support, structural guidance, and sites for cells adhesion, which are very important in new bone tissue regeneration, for example, in the porous tantalum (Ta) scaffolds which have been introduced as a metallic implant for bone defect therapy. Porous Ta scaffolds haves good stability, high volumetric porosity (70-80%), low modulus of elasticity (3 MPa), and high friction characteristics, which can improve bone ingrowth and bone mineral density.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The synthetic scaffolds have convenient sources, good safety and non-immunogenicity, therefore, various synthetic scaffolds such as inorganic ceramics, bone cements, and metal implants have been introduced as the substrates for bone defects. 5,6 These synthetic scaffolds provide physical support, structural guidance, and sites for cells adhesion, which are very important in new bone tissue regeneration, for example, in the porous tantalum (Ta) scaffolds which have been introduced as a metallic implant for bone defect therapy. Porous Ta scaffolds haves good stability, high volumetric porosity (70-80%), low modulus of elasticity (3 MPa), and high friction characteristics, which can improve bone ingrowth and bone mineral density.…”
Section: Introductionmentioning
confidence: 99%
“…[6,8] To solve thesep roblems, bone tissue engineering has emerged as ap romising technique for bone regeneration. [11][12][13] Inspired by natural bone, the composite porouss caffolds comprising organic polymers and inorganic materials have been designed to meet as many requirementsa sp ossible. [11][12][13] Inspired by natural bone, the composite porouss caffolds comprising organic polymers and inorganic materials have been designed to meet as many requirementsa sp ossible.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] An ideal bone tissue engineereds caffold should possess aw ell-interconnected porouss tructure for cell infiltration and mass transportation, good mechanical properties to withstand mechanicalloading and support the newly formed bone, and controlled degradability for new bone tissue ingrowth, and bioactivity for improved osteogenic activity. [11][12][13] Inspired by natural bone, the composite porouss caffolds comprising organic polymers and inorganic materials have been designed to meet as many requirementsa sp ossible. Importantly,t hese composite porouss caffolds can combinet he advantages of organic polymers and inorganic materials, which endows the scaffolds with great potential in bone-tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…32 A wide range of exogenous growth factors are currently being used in bone tissue engineering: transforming growth factor beta (TGF-b1), fibroblast growth factor (FGF), insulin growth factor (IGF), vascular endothelial growth factor (VEGF), PDGF, and bone morphogenic proteins (BMPs) etc. 33, 34 Wen B et al 35 have shown that application of BMP-2 (50μg) to Straumann Bone Ceramic leads to significant mineralisation and new bone formation compared the non-loaded scaffolds. As shown by Chang HC et al 36 BMP-loaded PLGA microspheres effectively promoted osteogenic potential of the gelatin/HA/β-TCP composite and facilitated supra-alveolar ridge augmentation in vivo.…”
Section: Components For Tissue Engineeringmentioning
confidence: 99%
“…For effective utilization, scaffolds still need modifications to impart biological cues that drive diverse cellular functions such as adhesion, migration, survival, proliferation, differentiation, and biomineralization. 34 A top-down approach for building bioactive and cell instructive biomaterial scaffolds is to create scaffold-ECM hybrid constructs by depositing extracellular matrix secreted by tissuespecific/stem cells on bare biomaterial scaffolds. Different synthetic materials have been used for scaffold construction.…”
Section: Tissue Engineering Selected Applicationmentioning
confidence: 99%